2012
DOI: 10.1002/app.36270
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization, and antimicrobial properties of new polystyrene‐bound Schiff bases and their some complexes

Abstract: This study investigated the antimicrobial properties of polymer‐bound Schiff bases and their Cu(II) and Ni(II) complexes. Novel polystyrene oligomer‐bound Schiff bases (FMPS‐Sch) were prepared from (4‐formyl‐3‐methoxyphenoxymethyl)polystyrene (FMPS) with cycloalkylaminothiophene derivatives and their Cu(II) and Ni(II) complexes have been synthesized and characterized. All these substances have been examined for antibacterial activity against pathogenic strains; Bacillus cereus, Listeria monocytogenes, Pseudomo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…The temperature changes in the TGA curves were above 100°C. Accordingly, it can be concluded that all polymeric microspheres do not contain crystal water …”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The temperature changes in the TGA curves were above 100°C. Accordingly, it can be concluded that all polymeric microspheres do not contain crystal water …”
Section: Resultsmentioning
confidence: 96%
“…The antibacterial and antifungal activities of the polymeric microspheres including azomethine ( 1a ‐ 1c and 2a ‐ 2c ) were studied by the well‐diffusion method against Bacillus cereus sp., Staphylococcus aureus (ATCC 25923), Staphylococcus epidermis (ATCC 12228), Micrococcus luteus (ATCC 93419), Listeria monocytogenes 4b (ATCC 19115), Salmonella typhi H (NCTC 901.8394), Brucella abortus (RSKK‐03026), Escherichia coli (ATCC 1230), Klebsiella pneumonia (ATCC 27853), Proteus vulgaris (RSKK 96026), and Candida albicans (Y‐1200‐NIH) . In this screening, DMF was used as solvent control.…”
Section: Methodsmentioning
confidence: 99%
“…Systemic fungal infections (including C. albicans) have emerged as significant causes of mortality and morbidity in immuno compromised patients (organ or ligament transplantation, cancer chemotherapy, adjuvants) [41,42]. All the compounds showed much inhibition activity against this yeast (Table 5, Fig.…”
Section: Antibacterial Activitiesmentioning
confidence: 99%
“…Schiff bases are known as electron-donating groups presence of nitrogen atom in which provide to form complexes with metals and also in many enzymatic reaction appear as an intermediate product (Metzler et al 1954, Snell & Jenkins 1959, Cordes & Jencks 1962. Recently, several studies have demonstrated that Schiff bases have biological activities such as antimutagenic, antibacterial (Nartop et al 2012, Sarı et al 2013). However, antimutagenic and antibacterial effects of these compounds has not been reported up to the present.…”
Section: Introductionmentioning
confidence: 99%